TÁLIM BASQA TILLERDE ALÍP BARÍLATUǴÍN KLASLARDA ÁDEBIY MATERIALLARDÍ OQÍTÍW METODIKASÍNÍŃ IZERTLENIWI - Mambetova, G.A. (SCIENCE and SOCIETY, 2023)
The article analyzes the subject, the object of the methodology of teaching literary criticism, the history of studying the methodology of teaching literary criticism, the study of the subject of the methodology of teaching literary materials in groups where teaching is conducted in other languages.